To the line of fire! : Mexican Texans and World War I - Ramírez, José A., 1975- (C.A. Brannen series, 2009)
"As author Jos? A. Ramirez demonstrates in To the line of fire!, the events of World War I and its aftermath would decisively transform the Tejano community, as war-hardened veterans returned with new, broadened perspectives. They led their people in opposing prejudice and discrimination, founded several civil rights groups, and eventually merged them into the League of United Latin American Citizens (LULAC), the largest and oldest surviving Hispanic civil rights organization in the United States. Ramirez also shows the diversity of reaction to the war on the part of the Tejano community: while some called enthusiastically for full participation in the war effort, others acted coolly, or only out of fear of reprisal. Similarly, the U.S. government, on the one hand, feared Tejanos might engage in anti-U.S. activity; on the other hand, the U.S. military displayed a cultural sensitivity toward Tejano soldiers that was remarkable for its time"--Jacket.